Água: o princípio da vida - Laranjeira, Sueli Aparecida Tabian (2008)
Since the end of the twentieth century and beginning of the XXI has been much researched on the water, issues of sanitation, shortage, rational consumption, pollution and its consequences. Paulo Freire (1998), argues that we act in the world with a series of practical knowledge that, upon being seized, habits become automated, thus reducing the curiosity. The children are growing with the view that it is normal to deforestation, hunger, poverty, corruption, violence, environmental degradation and, in a few years, the rationing of water - which in many countries is already a reality -- to be the most discussed topic in recent years throughout the media. This study sought to understand the importance of water for humans and lead the reader to reflect on how it is ingested and quality, from the individual to the collective, the experience of their day to day, aware that it each is responsible for the rational use of water. Human beings need to create a bond with the water and realize that it is essential to any kind of life. The low consumption of it is harmful to human health and can lead to serious problems. And this bond and connection with the water being consumed, how to handle and use should be developed in families and schools from early childhood education and elementary education. This work also contributes to the formation of citizens aware, able to decide and act in a social reality so committed to life, with the welfare of each individual and of society. More than concepts, families and schools need to work attitudes and values of training with the environment, especially with water.